Applied Bioinformatics - Selzer, Paul M.; Marhöfer, Richard J.; Koch, Oliver (Springer, 2018)
Though a relatively young discipline, bioinformatics is finding increasing importance in many life science disciplines, including biology, biochemistry, medicine, and chemistry. Since its beginnings in the late 1980s, the success of bioinformatics has been associated with rapid developments in computer science, not least in the relevant hardware and software. In addition, biotechnological advances, such as have been witnessed in the fields of genome sequencing, microarrays, and proteomics, have contributed enormously to the bioinformatics boom. Finally, the simultaneous breakthrough and success of the World Wide Web has facilitated the worldwide distribution of and easy access to bioinformatics tools. Today, bioinformatics techniques, such as the Basic Local Alignment Search Tool (BLAST) algorithm, pairwise and multiple sequence comparisons, queries of biological databases, and phylogenetic analyses, have become familiar tools to the natural scientist. Many of the software products that were initially unintuitive and cryptic have matured into relatively simple and user-friendly products that are easily accessible over the Internet. One no longer needs to be a computer scientist to proficiently operate bioinformatics tools with respect to complex scientific questions. Nevertheless, what remains important is an understanding of fundamental biological principles, together with a knowledge of the appropriate bioinformatics tools available and how to access them. Also and not least important is the confidence to apply these tools correctly in order to generate meaningful results.